Contrasting regimes for organic matter degradation in the East Siberian Sea and the Laptev Sea assessed through microbial incubations and molecular markers; Marine Chemistry; Vol. 170 - Karlsson E. S.; Brüchert V.; Tesi T.; Charkin A.; Dudarev O. V. Oleg Viktorovich; Semiletov I. P. Igor Petrovich; Gustafsson Ö (2015, 2015)
Title screen